2015
DOI: 10.1161/circresaha.116.305326
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Inward-Rectifier Potassium Current Upregulation in Profibrillatory Atrial Remodeling

Abstract: Rationale: Fibroblasts are involved in cardiac arrhythmogenesis and contribute to the atrial fibrillation substrate in congestive heart failure (CHF) by generating tissue fibrosis. Fibroblasts display robust ion currents, but their functional importance is poorly understood. Objective: To characterize atrial fibroblast inward-rectifier K + current ( I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 31 publications
3
60
1
1
Order By: Relevance
“…) and fibroblasts (Qi et al . ), the membrane potential of freshly isolated eCPCs is not set by Kir channels. We found that the resting membrane potential of c‐Kit + eCPCs depends predominantly on the intermediate‐conductance Ca 2+ ‐activated channel KCa3.1.…”
Section: Discussionmentioning
confidence: 99%
“…) and fibroblasts (Qi et al . ), the membrane potential of freshly isolated eCPCs is not set by Kir channels. We found that the resting membrane potential of c‐Kit + eCPCs depends predominantly on the intermediate‐conductance Ca 2+ ‐activated channel KCa3.1.…”
Section: Discussionmentioning
confidence: 99%
“…6 Non-coding RNAs (ncRNAs) comprise over 95% of the total RNA transcripts in eukaryotic cells. 17 MiR-23b-3p and miR-27b-3p are located within a single transcription unit from a microRNA cluster on human chromosome 9 (www.mirdb.org). 8 MicroRNA (miRNA) is an endogenous non-coding RNA with about 22 nucleotides and is involved in a variety of biological processes and diseases by inhibiting the protein translation process of the target gene.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the microscopic size of myocytes, further investigation is needed on whether this has any effect when progressing to organ scale. Another limitation of the tissue simulations is that only myocytes are considered: the fibroblast may play a role in modulating the excitation wave propagation in AF [49] and thus warrants future investigations incorporating fibroblasts into the model. A third limitation is that the present paper focuses only on idealised tissue with aligned fibres, uniform cell types and contact bond strength, as the main focus was the comparison of spiral wave properties amongst the three cases.…”
Section: Discussionmentioning
confidence: 99%